KARAKTERISASI RADIONUKLIDA PADA TIAP SUB-SISTEM KESELAMATAN REAKTOR DAYA BERBAHAN BAKAR MOX - Udiyani, Pande Made (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
Substitute UO2 fuel that low enrichment of uranium is that MOX fuel has a higher enrichment. MOX fuel has a content of plutonium and actinide nuclides a higher than UO2 fuel, which will produce different characteristics of radionuclides for each sub-system of power reactors. Analyzis of radionuclide for each safety sub-system at MOX power reactor aims to determine the characteristics of radionuclides, especially plutonium and actinides consequences. Analyzis has done by calculating and observing the radionuclide for each safety sub-system in normal operation and accident (small LOCA, large LOCA, and severe accident) on PWR-1000 reactors. It can concluded that the use of MOX fuel can add to the radiological consequences to the environment and public, mainly because a larger inventory of radionuclides, including transuranic radionuclides and the actinide group, among others: Pu-239, Am-241, Cm-242, Pu-240, Pu -241 and Pu-242.